Nanometer multilayer structure coating cutting tool and preparation method thereof

Through the design of nano-multilayer structure coating tools and physical vapor deposition process, the bond strength and wear resistance of coated tools in the processing of high-temperature alloys and titanium alloys are solved, and the high-temperature stability and long-life effect of the coating is achieved.

CN120464967APending Publication Date: 2025-08-12SHANGHAI YUANCHUANG TONGZHANG SURFACE COATING TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510810244.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

When processing high-temperature alloys or titanium alloys, existing coating tools have problems such as insufficient high-temperature oxidation resistance, poor thermal matching between layers and lack of multi-component design, resulting in low coating bonding strength, insufficient wear resistance and crack propagation resistance, affecting tool life.

Method used

Nano-multi-layer structural coatings are adopted, including WC coating, CrCN/WC functional layer, CrTaHfCN/CrCN/WC functional layer and CrTaHfCN surface layer. The physical vapor deposition process is precisely regulated to form a gradient, multi-scale nano alternating structure, and the composite carbon nitride of high melting point metal elements Ta and Hf is introduced to enhance the oxidation resistance and binding strength of the coating.

Benefits of technology

It significantly improves the oxidation resistance, high temperature resistance and wear resistance of the coating, extends the service life of the tool under severe working conditions, and is suitable for precision processing of titanium alloys and high temperature alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120464967A_ABST
    Figure CN120464967A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coated cutting tools, and provides a nano multilayer structure coated cutting tool and a preparation method thereof.The nano multilayer structure coated cutting tool comprises a base body and a nano multilayer structure coating deposited on the surface of the base body through a physical vapor deposition method, and the coating sequentially comprises a WC coating deposited on the base body, a WC coating deposited on the surface of the base body, a WC coating deposited on the surface of the base body and a WC coating deposited on the surface of the base The first CrCN / WC functional layer is composed of a first CrCN nano layer and a first WC nano layer which are alternately deposited; the second CrCN / WC functional layer is composed of a second CrCN nano layer and a second WC nano layer which are alternately deposited; the CrTaHfCN / CrCN / WC functional layer is formed by periodically and repeatedly depositing a first CrTaHfCN nano layer, a third CrCN nano layer and a third WC layer according to an ABC sequence; and a CrTaHfCN surface layer. According to the invention, the bonding strength between the layers is improved, and the oxidation resistance, high temperature resistance, wear resistance and crack propagation resistance of the coating are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coated cutting tools, and in particular relates to a nano multi-layer structure coated cutting tool and a preparation method thereof. Background Art

[0002] With the rapid development of high-end manufacturing sectors such as aerospace, energy equipment, and precision instruments, the demand for precision machining of high-strength, high-hardness materials such as titanium alloys and nickel-based superalloys is growing. Due to their excellent high-temperature strength, corrosion resistance, and low thermal conductivity, these materials are prone to severe tool wear, tool sticking, and work hardening during machining. This leads to low machining efficiency and shortened tool life, severely restricting the manufacturing quality and cost control of high-value-added components. To address this challenge, coated tool technology, as a core means of improving cutting performance, has gradually become a research hotspot in modern manufacturing.

[0003] Traditional coated tools usually use single-layer or simple multi-layer structures such as TiN, TiAlN, and CrN, and form a protective layer on the surface of cemented carbide or ceramic substrates through physical vapor deposition (PVD) or chemical vapor deposition (CVD) technology. Although such coatings can improve the hardness and wear resistance of tools to a certain extent, they still face significant limitations when processing high-temperature alloys or titanium alloys: First, conventional coating materials (such as TiAlN) are prone to oxidation failure in high-temperature environments (>800°C), resulting in a sudden drop in coating hardness and an increase in friction coefficient; second, single-layer coatings have poor crack propagation resistance, and the difference in thermal expansion coefficient with the substrate can easily cause interfacial stress concentration, accelerating coating spalling; third, during high-speed cutting, the intense friction and chemical interaction between the coating and the workpiece material can induce diffusion wear and bonding failure, further shortening tool life.

[0004] In recent years, nanostructured multilayer coatings have attracted widespread attention due to their unique interface effects and designable properties. By alternately depositing two or more nanoscale heterogeneous material layers, grain refinement can be effectively achieved, dislocation motion can be hindered, and a synergistic improvement in coating hardness and toughness can be achieved. In addition, reasonable composition gradient design and interface structure optimization can improve the thermal stability and oxidation resistance of the coating. However, existing nanostructured multilayer coatings still face the following bottlenecks when facing extreme processing conditions:

[0005] 1. Insufficient high-temperature oxidation resistance: Most nano-multilayer systems (such as TiAlN / CrN) are still difficult to inhibit the diffusion of oxygen elements along the interlayer at high temperatures, resulting in loose coating structure and reduced protective performance;

[0006] 2. Poor thermal matching between layers: The difference in thermal expansion coefficients of different material layers can easily cause micro cracks between layers under cyclic thermal loads, reducing the bonding strength of the coating;

[0007] 3. Lack of multi-component composite design: The existing coating system has insufficient exploration of the combination of new materials such as high entropy alloys and multi-component nitrogen / carbides, and has failed to fully tap the potential of multi-component synergistic strengthening.

[0008] To address the above problems, it is urgent to start from the two aspects of coating composition innovation and structural optimization to develop a nano-composite coating system with high hardness, excellent oxidation resistance and high-temperature stability. Summary of the Invention

[0009] In order to solve the problems existing in the above-mentioned prior art, the main purpose of the present invention is to propose a nano multilayer structure coating tool and its preparation method, breaking through the bottleneck of the prior art in the cutting of high-performance difficult-to-process materials, which is of great significance to promoting the advancement of high-end equipment manufacturing technology. The present invention can effectively improve the high-temperature oxidation resistance of the coating by introducing high-melting point metal elements (such as Ta, Hf) and their composite carbonitrides; and constructing a gradient, multi-scale nano-alternating structure helps to relieve interface stress and inhibit crack propagation, thereby extending the service life of the tool under harsh working conditions. In addition, the precise control of the physical vapor deposition process parameters to achieve a balance between coating density, interface bonding strength and residual stress is the key to ensuring the stability of coating performance.

[0010] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0011] A nano multilayer structure coating tool, comprising:

[0012] A substrate and a nano multilayer structure coating deposited on the surface of the substrate by a physical vapor deposition method, wherein the nano multilayer structure coating comprises, from the inside to the outside:

[0013] a WC coating deposited on the substrate;

[0014] a first CrCN / WC functional layer composed of alternately deposited first CrCN nanolayers and first WC nanolayers;

[0015] a second CrCN / WC functional layer composed of alternately deposited second CrCN nanolayers and second WC nanolayers;

[0016] A CrTaHfCN / CrCN / WC functional layer, which is formed by periodically and repeatedly depositing a first CrTaHfCN nanolayer, a third CrCN nanolayer, and a third WC layer in an ABC sequence; and

[0017] CrTaHfCN surface layer;

[0018] The atomic ratio of C / W in the WC coating is 0.8 to 0.9;

[0019] The atomic ratios of C / Cr and N / Cr in the first CrCN nanolayer are 0.6 to 0.8 and 0.9 to 1.1, respectively;

[0020] The atomic ratio of Cr, Ta, Hf, C, and N in the first CrTaHfCN nanolayer is 1.0: 0.15-0.25: 0.05-0.15: 0.18-0.23: 0.47-0.52;

[0021] The C / W atomic ratio in the WC coating, the first WC nanolayer, the second WC nanolayer and the third WC nanolayer increases gradually at an interval of 0.1;

[0022] The C / Cr atomic ratio in the first CrCN nanolayer, the second CrCN nanolayer and the third CrCN nanolayer increases in a gradient of 0.2, and the N / Cr atomic ratio decreases in a gradient of 0.2.

[0023] As a preferred embodiment of the nano-multilayer structure coated tool described in the present invention, the atomic ratio of Cr, Ta, Hf, C, and N in the CrTaHfCN surface layer is 1.0: 0.15-0.25: 0.05-0.15: 0.23-0.28: 0.42-0.47; the C / Cr atomic ratio in the first CrTaHfCN nanolayer and the CrTaHfCN surface layer increases gradually at an interval of 0.05, and the N / Cr atomic ratio decreases gradually at an interval of 0.05.

[0024] As a preferred embodiment of the nano-multilayer structure coated tool described in the present invention, the thickness of the first CrCN / WC functional layer is 10±2 nm, and the number of layers is 25 to 63; the thickness of the second CrCN / WC functional layer is 20±2 nm, and the number of layers is 22 to 39; the thickness of the CrTaHfCN / CrCN / WC functional layer is 30±2 nm, and the number of layers is 23 to 33.

[0025] As a preferred solution of the nano multi-layer structure coating tool described in the present invention, the total thickness of the nano multi-layer structure coating is 2.95 to 4.05 μm.

[0026] As a preferred embodiment of the nano-multilayer structure coated tool described in the present invention, the thickness of the WC coating is 0.15 to 0.25 μm; the total thickness of the first CrCN / WC functional layer is 0.3 to 0.5 μm; the total thickness of the second CrCN / WC functional layer is 0.5 to 0.7 μm; the total thickness of the CrTaHfCN / CrCN / WC functional layer is 0.7 to 0.9 μm; and the thickness of the CrTaHfCN surface layer is 1.3 to 1.7 μm.

[0027] As a preferred embodiment of the nano-multilayer structure coated tool described in the present invention, the first CrCN nanolayer, the second CrCN nanolayer and the third CrCN nanolayer are all CrCN solid solution phases and have a cubic crystal structure; the first CrTaHfCN nanolayer is a CrTaHfCN solid solution phase and has a cubic crystal structure.

[0028] As a preferred embodiment of the nano-multilayer structure coated tool described in the present invention, in which: in the first CrCN / WC functional layer, the grain sizes of the first CrCN nanolayer and the first WC nanolayer are both 8 to 12 nm; in the second CrCN / WC functional layer, the grain sizes of the second CrCN nanolayer and the second WC nanolayer are both 18 to 22 nm; in the CrTaHfCN / CrCN / WC functional layer, the grain sizes of the first CrTaHfCN nanolayer, the third CrCN nanolayer and the third WC nanolayer are all 28 to 32 nm.

[0029] As a preferred solution of the nano multilayer structure coating tool described in the present invention, the WC coating has a hexagonal crystal structure and a grain size of 8 to 12 nm.

[0030] As a preferred solution of the nano multilayer structure coating tool described in the present invention, the CrTaHfCN surface layer has a cubic crystal structure and a grain size of 30 to 50 nm.

[0031] As a preferred embodiment of the nano multilayer structure coating tool of the present invention, the hardness of the WC coating is 30.8-31.2 GPa, and the fracture toughness is 4.9-5.1 MPa·m 1 / 2 The hardness of the first CrCN / WC functional layer is 29.8~30.2GPa, and the fracture toughness is 6.5~6.7MPa·m 1 / 2 The hardness of the second CrCN / WC functional layer is 29.8~30.2GPa, and the fracture toughness is 6.9~7.1MPa·m 1 / 2 The hardness of the CrTaHfCN / CrCN / WC functional layer is 31.8~32.2GPa, and the fracture toughness is 8.0~8.2MPa·m 1 / 2 The hardness of the CrTaHfCN surface layer is 32.8~33.2GPa, and the fracture toughness is 8.9~9.1MPa·m 1 / 2 .

[0032] To solve the above technical problems, according to another aspect of the present invention, the present invention provides the following technical solutions:

[0033] A method for preparing the above-mentioned nano-multilayer structure coating tool is to deposit the nano-multilayer structure coating on a substrate by a physical vapor deposition method, comprising:

[0034] S1. Deposit a WC coating on the substrate with the following process parameters: temperature of 480-500°C, Ar partial pressure of 0.3-0.4 Pa, CH4 partial pressure of 3.1-3.2 Pa, substrate bias of 43-47 V, W target current of 195-205 A, and disk speed of 3.5 rpm.

[0035] S2. Depositing a first CrCN / WC functional layer on the WC coating, wherein the process parameters are as follows: depositing a first CrCN nanolayer in the first CrCN / WC functional layer at a temperature of 480-500° C., an Ar partial pressure of 0.3-0.4 Pa, a CH4 partial pressure of 2.5-2.6 Pa, a N2 partial pressure of 0.6-0.7 Pa, a substrate bias of 48-52 V, a Cr target current of 155-165 A, and a disk rotation speed of 3.5 r / min; depositing a first WC nanolayer in the first CrCN / WC functional layer at a temperature of 480-500° C., an Ar partial pressure of 0.3-0.4 Pa, a CH4 partial pressure of 2.5-2.6 Pa, a N2 partial pressure of 0.6-0.7 Pa, a substrate bias of 48-52 V, a W target current of 195-205 A, and a disk rotation speed of 3.5 r / min;

[0036] S3. Depositing a second CrCN / WC functional layer on the first CrCN / WC functional layer, wherein the process parameters are as follows: depositing a second CrCN nanolayer in the second CrCN / WC functional layer at a temperature of 480-500° C., an Ar partial pressure of 0.3-0.4 Pa, a CH4 partial pressure of 4-4.1 Pa, a N2 partial pressure of 1.6-1.7 Pa, a substrate bias of 53-57 V, a Cr target current of 155-165 A, and a disk rotation speed of 3 r / min; and depositing a second WC nanolayer in the second CrCN / WC functional layer at a temperature of 480-500° C., an Ar partial pressure of 0.3-0.4 Pa, a CH4 partial pressure of 4-4.1 Pa, a N2 partial pressure of 1.6-1.7 Pa, a substrate bias of 53-57 V, a W target current of 195-205 A, and a disk rotation speed of 3 r / min;

[0037] S4, the deposition parameters of the CrTaHfCN / CrCN / WC functional layer deposited on the second CrCN / WC functional layer are as follows: at a temperature of 480-500°C, an Ar partial pressure of 0.3-0.4Pa, a CH4 partial pressure of 5.5-5.6Pa, a N2 partial pressure of 2.6-2.7Pa, a substrate bias of 58-62V, a CrTaHf target current of 175-185A and a large disk speed of 2.5r / min, the first CrTaHfCN nanolayer in the CrTaHfCN / CrCN / WC functional layer is deposited; at a temperature of 480-500°C, an Ar partial pressure of 0.3-0.4Pa, a CH4 partial pressure of 5.5-5.6Pa, a N2 partial pressure of 2.6-2.7Pa, a substrate bias of 58-62V, a CrTaHf target current of 175-185A and a large disk speed of 2.5r / min, the first CrTaHfCN nanolayer in the CrTaHfCN / CrCN / WC functional layer is deposited; a. The third CrCN nanolayer in the CrTaHfCN / CrCN / WC functional layer was deposited under the conditions of N2 partial pressure of 2.6-2.7Pa, substrate bias of 58-62V, Cr target current of 155-165A and disk rotation speed of 2.5r / min; the third WC nanolayer in the CrTaHfCN / CrCN / WC functional layer was deposited under the conditions of temperature of 480-500℃, Ar partial pressure of 0.3-0.4Pa, CH4 partial pressure of 5.5-5.6Pa, N2 partial pressure of 2.6-2.7Pa, substrate bias of 58-62V, W target current of 195-205A and disk rotation speed of 2.5r / min;

[0038] S5. Deposit a CrTaHfCN surface layer on the CrTaHfCN / CrCN / WC functional layer with the following process parameters: temperature of 480-500°C, Ar partial pressure of 0.3-0.4 Pa, CH4 partial pressure of 6-6.1 Pa, N2 partial pressure of 2.6-2.7 Pa, substrate bias of 63-67 V, CrTaHf target current of 175-185 A, and disk speed of 2 r / min.

[0039] The beneficial effects of the present invention are as follows:

[0040] The present invention provides a nano-multilayer structure coating tool and a preparation method thereof, comprising a substrate and a nano-multilayer structure coating deposited on the surface of the substrate by a physical vapor deposition method. The nano-multilayer structure coating comprises, from the inside to the outside, a WC coating deposited on the substrate; a first CrCN / WC functional layer comprising a first CrCN nanolayer and a first WC nanolayer; a second CrCN / WC functional layer comprising a second CrCN nanolayer and a second WC nanolayer; a CrTaHfCN / CrCN / WC functional layer comprising a first CrTaHfCN nanolayer, a third CrCN nanolayer and a third WC nanolayer; and a CrTaHfCN surface layer. The present invention improves the bonding strength between the coating and the substrate, and between the coatings, achieves a gradient change in hardness and toughness from the bottom layer to the surface layer of the coating, significantly improves the coating's oxidation resistance, high temperature resistance, wear resistance, and crack propagation resistance, and is suitable for the precision machining of high-value-added materials such as titanium alloys and high-temperature alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0042] Figure 1 It is a schematic cross-sectional view of the nano multilayer structure coating tool of the present invention.

[0043] The reference numerals are as follows:

[0044] 100 matrix;

[0045] 200 WC coating;

[0046] 300 first CrCN / WC functional layer; 301 first CrCN nanolayer; 302 first WC nanolayer;

[0047] 400 second CrCN / WC functional layer; 401 second CrCN nanolayer; 402 second WC nanolayer;

[0048] 500CrTaHfCN / CrCN / WC functional layer; 501 first CrTaHfCN nanolayer; 502 third CrCN nanolayer; 503 third WC nanolayer;

[0049] 600CrTaHfCN surface layer.

[0050] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings and in conjunction with the embodiments. DETAILED DESCRIPTION

[0051] The following will be a clear and complete description of the technical solutions in the embodiments. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0052] like Figure 1 As shown, the present invention provides a nano-multilayer structure coating tool, including a substrate 100 and a nano-multilayer structure coating deposited on the surface of the substrate 100 by a physical vapor deposition method. The substrate 100 is made of any one of cemented carbide, high-speed steel, cermet, polycrystalline diamond, cubic boron nitride, etc. The nano-multilayer structure coating includes, from the inside to the outside, a WC coating 200 deposited on the substrate 100, a first CrCN / WC functional layer 300, a second CrCN / WC functional layer 400, a CrTaHfCN / CrCN / WC functional layer 500 and a CrTaHfCN surface layer 600. The first CrCN / WC functional layer 300 is composed of alternately deposited first CrCN nanolayers 301 and first WC nanolayers 302; the second CrCN / WC functional layer 400 is composed of alternately deposited second CrCN nanolayers 401 and second WC nanolayers 402; the CrTaHfCN / CrCN / WC functional layer is composed of a first CrTaHfCN nanolayer 501, a third CrCN nanolayer 502 and a third WC layer 503 periodically deposited in an ABC sequence.

[0053] The preparation method of a nano multilayer structure coating tool comprises the following steps:

[0054] S0. Substrate preparation: The substrate to be coated is pre-treated by cleaning, degreasing, and rust removal to ensure that the substrate surface is clean and free of impurities.

[0055] S1. WC coating deposition: The pretreated substrate is placed in a PVD coating furnace, and a WC coating is deposited on the substrate surface by ion bombardment. As a transition layer that directly contacts the substrate, the WC coating must ensure high density to reduce interface defects, while avoiding excessive thickness that causes stress concentration caused by differences in the coefficient of thermal expansion (CTE) of the substrate. The thickness is 0.15 to 0.25 μm, taking into account both interface bonding strength and stress release.

[0056] S2. Deposition of the first CrCN / WC functional layer: The first CrCN / WC functional layer is deposited on top of the WC coating. The first CrCN / WC functional layer enhances the coating's lubricity and corrosion resistance. Because its composition and grain size are similar to those of the WC coating, the two exhibit good bonding strength. A large number of interfaces are formed through the nano-alternating structure, utilizing the Hall-Petch effect to increase hardness while deflecting cracks at the interfaces to improve toughness. The thickness is 0.3-0.5 μm, ensuring a sufficient number of interfaces for interface strengthening.

[0057] S3. Deposition of the Second CrCN / WC Functional Layer: A second CrCN / WC functional layer is deposited on top of the first CrCN / WC functional layer. The second CrCN / WC functional layer further enhances the coating's lubricity and corrosion resistance. Because its composition is identical to the first CrCN / WC functional layer, the two layers exhibit good bonding strength. The thickness is 0.5-0.7 μm. Further increasing the thickness of the nano-alternating layer reduces interlayer stress mutations through gradient composition and structural continuity.

[0058] S4, CrTaHfCN / CrCN / WC functional layer: On top of the second CrCN / WC functional layer, the CrTaHfCN / CrCN / WC functional layer is deposited. The CrTaHfCN / CrCN / WC functional layer can further enhance the lubricity and corrosion resistance of the coating, while also improving its oxidation resistance and wear resistance. Moreover, because its composition is similar to that of the second CrCN / WC functional layer, the two have good bonding strength. In addition, the CrTaHfCN / CrCN / WC functional layer also introduces Ta / Hf elements to form multi-component nitrides, which synergistically improve the high-temperature hardness through solid solution strengthening and nano-multilayer structure. The thickness is 0.7 to 0.9 μm. The coating containing Ta / Hf needs to be thick enough (>0.5 μm) to ensure the formation of a continuous protective oxide at high temperatures.

[0059] S5. CrTaHfCN surface layer deposition: A CrTaHfCN surface layer is deposited on top of the CrTaHfCN / CrCN / WC functional layer. The CrTaHfCN surface layer further enhances the coating's lubricity and corrosion resistance, while also improving its oxidation and wear resistance. Furthermore, due to its similar composition and grain size to the CrTaHfCN / CrCN / WC functional layer, the two exhibit good bonding strength. The surface layer, with a thickness of 1.3 to 1.7 μm, typically accounts for 30% to 50% of the total coating thickness. As a functional layer in direct contact with the workpiece material, it requires sufficient thickness to resist long-term wear and high-temperature oxidation.

[0060] S6. Post-processing: After the coating deposition is completed, post-processing such as sandblasting and polishing is carried out to eliminate the stress inside the coating, thereby improving the adhesion and stability of the coating.

[0061] In summary, the good bonding between the above coatings and the substrate, and between the coatings, can minimize the peeling of the coatings caused by internal stress problems.

[0062] The technical solution of the present invention is further described below with reference to specific embodiments.

[0063] Example 1

[0064] A nano multilayer structure coating tool and a preparation method thereof, wherein the substrate is a WNMG 080408E-MC3 type cemented carbide, comprising the following steps:

[0065] S0. Substrate preparation: The substrate to be coated is pre-treated by cleaning, degreasing, and rust removal to ensure that the substrate surface is clean and free of impurities.

[0066] S1. WC Coating Deposition: The pretreated substrate was placed in a PVD coating furnace and a WC coating was deposited on the substrate surface by ion bombardment. The WC coating was deposited at a temperature of 490°C, an Ar partial pressure of 0.35 Pa, a CH4 partial pressure of 3.15 Pa, a substrate bias of 45 V, a W target current of 200 A, and a disk rotation speed of 3.5 r / min. The thickness was 0.2 μm, and the atomic ratio of W to C was 1.0:0.85.

[0067] S2. Deposition of the First CrCN / WC Functional Layer: A first CrCN / WC functional layer with excellent lubricity and corrosion resistance was deposited on the WC coating. The first CrCN / WC functional layer was deposited at a temperature of 490°C, an Ar partial pressure of 0.35 Pa, a CH4 partial pressure of 2.55 Pa, a N2 partial pressure of 0.65 Pa, a substrate bias of 50 V, a Cr target current of 160 A, a W target current of 200 A, and a disk rotation speed of 3.5 r / min. The thickness of the first CrCN / WC functional layer was 0.4 μm (single layer thickness 10 nm, total 40 layers). The atomic ratio of Cr, C, and N in the first CrCN nanolayer was 1.0:0.7:1.0, and the atomic ratio of W to C in the first WC nanolayer was 1.0:0.95.

[0068] S3. Deposition of a Second CrCN / WC Functional Layer: A second CrCN / WC functional layer with excellent lubricity and corrosion resistance was deposited on top of the first CrCN / WC functional layer. The second CrCN / WC functional layer was deposited at a temperature of 490°C, an Ar partial pressure of 0.35 Pa, a CH4 partial pressure of 4.05 Pa, a N2 partial pressure of 1.65 Pa, a substrate bias of 55 V, a Cr target current of 160 A, a W target current of 200 A, and a disk rotation speed of 3 r / min. The thickness of the second CrCN / WC functional layer was 0.6 μm (single layer thickness 20 nm, total 30 layers). The atomic ratio of Cr, C, and N in the second CrCN nanolayer was 1.0:0.9:0.8, and the atomic ratio of W to C in the second WC nanolayer was 1.0:1.05.

[0069] S4, CrTaHfCN / CrCN / WC functional layer: On the second CrCN / WC functional layer, the first CrTaHfCN nanolayer, the third CrCN nanolayer and the third WC layer are periodically and repeatedly deposited in an ABC order to obtain a CrTaHfCN / CrCN / WC functional layer with excellent lubricity, corrosion resistance, oxidation resistance and wear resistance. The CrTaHfCN / CrCN / WC functional layer was deposited at a temperature of 490°C, an Ar partial pressure of 0.35 Pa, a CH4 partial pressure of 5.55 Pa, a N2 partial pressure of 2.65 Pa, a substrate bias of 60 V, a CrTaHf target current of 180 A, a Cr target current of 160 A, a W target current of 200 A, and a disk rotation speed of 2.5 r / min. Its thickness was 0.8 μm (single layer thickness 30 nm, a total of 27 layers). The atomic ratio of Cr, Ta, Hf, C, and N in the first CrTaHfCN nanolayer was 1.0:0.2:0.1:0.2:0.5, the atomic ratio of Cr, C, and N in the third CrCN nanolayer was 1.0:1.1:0.6, and the atomic ratio of W and C in the third WC nanolayer was 1.0:1.15.

[0070] S5. CrTaHfCN surface layer deposition: A CrTaHfCN surface layer with excellent lubricity, corrosion resistance, oxidation resistance, and wear resistance was deposited on top of the CrTaHfCN / CrCN / WC functional layer. The CrTaHfCN surface layer was deposited at a temperature of 490°C, an Ar partial pressure of 0.35 Pa, a CH4 partial pressure of 6.05 Pa, a N2 partial pressure of 2.65 Pa, a substrate bias of 65 V, a CrTaHf target current of 180 A, and a disk rotation speed of 2 r / min. The thickness of the CrTaHfCN surface layer was 1.5 μm, and the atomic ratio of Cr, Ta, Hf, C, and N was 1.0:0.2:0.1:0.25:0.45.

[0071] S6. Post-processing: After the coating deposition is completed, post-processing such as sandblasting and polishing is carried out to eliminate the stress inside the coating, thereby improving the adhesion and stability of the coating.

[0072] Comparative Example 1

[0073] The difference from Example 1 is that step S2 is not performed, and the deposition thickness of the CrCN / WC nano-alternating coating in step S3 is increased to 1 μm.

[0074] Comparative Example 2

[0075] The difference from Example 1 is that step S4 is not performed, and the thickness of the CrTaHfCN surface layer in step S5 is increased to 2.3 μm.

[0076] Example 2

[0077] The difference from Example 1 is that the substrate is RPHT 1204M8E-MM3 cemented carbide.

[0078] Comparative Example 3

[0079] A single-layer AlTiN coated cutting tool and a preparation method thereof, wherein the substrate is a WNMG 080408E-MC3 cemented carbide, comprising the following steps:

[0080] S0. Substrate preparation: The substrate to be coated is pre-treated by cleaning, degreasing, and rust removal to ensure that the substrate surface is clean and free of impurities.

[0081] S1. AlTiN coating deposition: The pretreated substrate is placed in a PVD coating furnace and an AlTiN coating is deposited on the substrate surface by ion bombardment. The AlTiN coating is deposited at a temperature of 490°C, a N2 partial pressure of 3.5 Pa, a substrate bias of 60 V, an AlTi target current of 200 A, and a disk speed of 2 r / min. The thickness of the AlTiN coating is 3.5 μm, and the atomic ratio of Al, Ti, and N is 1.0:0.67:1.5.

[0082] S2. Post-processing: After the coating deposition is completed, post-processing such as sandblasting and polishing is carried out to eliminate the stress inside the coating, thereby improving the adhesion and stability of the coating.

[0083] Comparative Example 4

[0084] A CrN / AlTiN nano-alternating coating tool and a preparation method thereof, wherein the substrate is a WNMG 080408E-MC3 type cemented carbide, comprising the following steps:

[0085] S0. Substrate preparation: The substrate to be coated is pre-treated by cleaning, degreasing, and rust removal to ensure that the substrate surface is clean and free of impurities.

[0086] S1. CrN coating deposition: The pretreated substrate was placed in a PVD coating furnace and a CrN coating was deposited on the substrate surface by ion bombardment. The CrN coating was deposited at a temperature of 490°C, a N2 partial pressure of 3.5 Pa, a substrate bias of 40 V, a Cr target current of 160 A, and a disk rotation speed of 2 r / min. The thickness of the CrN coating was 1 μm, and the atomic ratio of Cr to N was 1.0:1.7.

[0087] S2. Deposition of CrN / AlTiN nano-alternating layers: A CrN / AlTiN nano-alternating layer was deposited on top of the CrN coating. The CrN / AlTiN nano-alternating layer was deposited at a temperature of 490°C, a N2 partial pressure of 3.5 Pa, a substrate bias of 60 V, a Cr target current of 160 A, an AlTi target current of 200 A, and a disk rotation speed of 2 r / min. The thickness of the layer was 1 μm. The atomic ratio of Cr to N in the CrN nano-layer was 1.0:1.7, and the atomic ratio of Al to Ti to N in the AlTiN nano-layer was 1.0:0.67:1.5.

[0088] S3. AlTiN coating deposition: An AlTiN coating was deposited on top of the CrN / AlTiN nano-alternating layer. The AlTiN coating was deposited at a temperature of 490°C, a N2 partial pressure of 3.5 Pa, a substrate bias of 80 V, an AlTi target current of 200 A, and a disk rotation speed of 2 r / min. The thickness of the AlTiN coating was 1.5 μm, and the atomic ratio of Al, Ti, and N was 1.0:0.67:1.5.

[0089] S4. Post-processing: After the coating deposition is completed, post-processing such as sandblasting and polishing is carried out to eliminate the stress inside the coating, thereby improving the adhesion and stability of the coating.

[0090] The performance of the cutting tools prepared in the embodiments and comparative examples was tested, and the results are shown in Table 1.

[0091] Table 1

[0092]

[0093] The following tests were conducted on the processing performance of the cutting tools prepared by various embodiments and comparative examples of the present invention, wherein:

[0094] Test condition 1 is as follows:

[0095] Operation: Turning

[0096] Workpiece: cylindrical parts

[0097] Material: TC6

[0098] Cutting speed: 100m / min

[0099] Feed: 0.1mm / rev

[0100] Cutting depth: 0.3mm

[0101] Wet cutting

[0102] The wear volume VB (unit: mm) after cutting for 20 minutes, 30 minutes, 40 minutes, 60 minutes and 70 minutes is shown in Table 2 below (- indicates failure).

[0103] Table 2

[0104] 20min 30min 40min 60min 70 minutes Example 1 0.08 0.12 0.16 0.25 0.30 Comparative Example 1 0.10 0.15 0.20 0.29 -- Comparative Example 2 0.13 0.20 0.31 -- --

[0105] It can be seen that under the same cutting conditions and cutting time, the wear of the tool prepared in Example 1 is significantly lower than that in Comparative Examples 1-2, indicating that the present invention greatly improves the service life of the tool.

[0106] Test condition 2 is as follows:

[0107] Operation: Face milling

[0108] Workpiece: Block

[0109] Material: GH4169

[0110] Cutting speed: 50m / min

[0111] Feed: 0.05mm / t

[0112] Cutting depth: 0.8mm

[0113] Wet cutting

[0114] The wear volume VB (unit: mm) after cutting for 10 minutes, 20 minutes, 30 minutes, 40 minutes and 50 minutes is measured and shown in Table 3 below (- indicates failure).

[0115] Table 3

[0116] 10min 20min 30min 40min 50min Example 2 0.05 0.09 0.13 0.16 0.21 Comparative Example 3 0.08 0.15 0.21 -- -- Comparative Example 4 0.07 0.13 0.19 -- --

[0117] It can be seen that under the same cutting conditions and cutting time, the wear of the tool prepared in Example 2 is significantly lower than that in Comparative Examples 3-4, indicating that the present invention greatly improves the service life of the tool.

[0118] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. All equivalent structural transformations made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A nano multilayer coating tool, characterized in that: include: A substrate and a nano multilayer structure coating deposited on the surface of the substrate by a physical vapor deposition method, wherein the nano multilayer structure coating comprises, from the inside to the outside: a WC coating deposited on the substrate; a first CrCN / WC functional layer composed of alternately deposited first CrCN nanolayers and first WC nanolayers; a second CrCN / WC functional layer consisting of alternately deposited second CrCN nanolayers and second WC nanolayers; A CrTaHfCN / CrCN / WC functional layer, which is formed by periodically and repeatedly depositing a first CrTaHfCN nanolayer, a third CrCN nanolayer, and a third WC layer in an ABC sequence; and CrTaHfCN surface layer; the atomic ratio of C / W in the WC coating is 0.8 to 0.9; The atomic ratios of C / Cr and N / Cr in the first CrCN nanolayer are 0.6 to 0.8 and 0.9 to 1.1, respectively; The atomic ratio of Cr, Ta, Hf, C, and N in the first CrTaHfCN nanolayer is 1.0: 0.15-0.25: 0.05-0.15: 0.18-0.23: 0.47-0.52; The C / W atomic ratio in the WC coating, the first WC nanolayer, the second WC nanolayer and the third WC nanolayer increases gradually at an interval of 0.1; The C / Cr atomic ratio in the first CrCN nanolayer, the second CrCN nanolayer and the third CrCN nanolayer increases in a gradient of 0.2, and the N / Cr atomic ratio decreases in a gradient of 0.

2.

2. The nano multilayer structure coating tool according to claim 1, characterized in that: The atomic ratio of Cr, Ta, Hf, C, and N in the CrTaHfCN surface layer is 1.0: 0.15-0.25: 0.05-0.15: 0.23-0.28: 0.42-0.47; wherein the C / Cr atomic ratio in the first CrTaHfCN nanolayer and the CrTaHfCN surface layer increases gradually at an interval of 0.05, and the N / Cr atomic ratio decreases gradually at an interval of 0.

05.

3. The nano multilayer structure coating tool according to claim 1, characterized in that: The single layer thickness of the first CrCN / WC functional layer is 10±2 nm, and the number of layers is 25 to 63; the single layer thickness of the second CrCN / WC functional layer is 20±2 nm, and the number of layers is 22 to 39; the single layer thickness of the CrTaHfCN / CrCN / WC functional layer is 30±2 nm, and the number of layers is 23 to 33.

4. The nano multilayer structure coating tool according to claim 1, characterized in that: The total thickness of the nano multi-layer structure coating is 2.95-4.05 μm.

5. The nano multilayer coating tool according to claim 1, characterized in that: The thickness of the WC coating is 0.15 to 0.25 μm; the total thickness of the first CrCN / WC functional layer is 0.3 to 0.5 μm; the total thickness of the second CrCN / WC functional layer is 0.5 to 0.7 μm; the total thickness of the CrTaHfCN / CrCN / WC functional layer is 0.7 to 0.9 μm; and the thickness of the CrTaHfCN surface layer is 1.3 to 1.7 μm.

6. The nano multilayer structure coating tool according to claim 1, characterized in that: The first CrCN nanolayer, the second CrCN nanolayer and the third CrCN nanolayer are all CrCN solid solution phases and have a cubic crystal structure; the first CrTaHfCN nanolayer is a CrTaHfCN solid solution phase and has a cubic crystal structure.

7. The nano multilayer structure coating tool according to claim 1, characterized in that: In the first CrCN / WC functional layer, the grain sizes of the first CrCN nanolayer and the first WC nanolayer are both 8 to 12 nm; in the second CrCN / WC functional layer, the grain sizes of the second CrCN nanolayer and the second WC nanolayer are both 18 to 22 nm; in the CrTaHfCN / CrCN / WC functional layer, the grain sizes of the first CrTaHfCN nanolayer, the third CrCN nanolayer, and the third WC nanolayer are all 28 to 32 nm.

8. The nano multilayer structure coating tool according to claim 1, characterized in that: The WC coating has a hexagonal crystal structure and a grain size of 8 to 12 nm.

9. The nano multi-layer structure coating tool according to claim 1, characterized in that: The CrTaHfCN surface layer has a cubic crystal structure and a grain size of 30 to 50 nm.

10. The nano multi-layer structure coating tool according to claim 1, characterized in that: The hardness of the WC coating is 30.8-31.2 GPa, and the fracture toughness is 4.9-5.1 MPa·m 1 / 2 The hardness of the first CrCN / WC functional layer is 29.8~30.2GPa, and the fracture toughness is 6.5~6.7MPa·m 1 / 2 The hardness of the second CrCN / WC functional layer is 29.8~30.2GPa, and the fracture toughness is 6.9~7.1MPa·m 1 / 2 The hardness of the CrTaHfCN / CrCN / WC functional layer is 31.8~32.2GPa, and the fracture toughness is 8.0~8.2MPa·m 1 / 2 The hardness of the CrTaHfCN surface layer is 32.8~33.2GPa, and the fracture toughness is 8.9~9.1MPa·m 1 / 2 .

11. A method for preparing a tool with a nano multilayer coating according to any one of claims 1 to 10, wherein the nano multilayer coating is deposited on a substrate by a physical vapor deposition method, characterized in that: include: S1. Depositing a WC coating on the substrate with the following process parameters: temperature of 480-500°C, Ar partial pressure of 0.3-0.4 Pa, CH4 partial pressure of 3.1-3.2 Pa, substrate bias voltage of 43-47 V, W target current of 195-205 A, and disk speed of 3.5 rpm; S2. Depositing a first CrCN / WC functional layer on the WC coating, wherein the process parameters are as follows: depositing a first CrCN nanolayer in the first CrCN / WC functional layer at a temperature of 480-500° C., an Ar partial pressure of 0.3-0.4 Pa, a CH4 partial pressure of 2.5-2.6 Pa, a N2 partial pressure of 0.6-0.7 Pa, a substrate bias of 48-52 V, a Cr target current of 155-165 A, and a disk rotation speed of 3.5 r / min; depositing a first WC nanolayer in the first CrCN / WC functional layer at a temperature of 480-500° C., an Ar partial pressure of 0.3-0.4 Pa, a CH4 partial pressure of 2.5-2.6 Pa, a N2 partial pressure of 0.6-0.7 Pa, a substrate bias of 48-52 V, a W target current of 195-205 A, and a disk rotation speed of 3.5 r / min; S3. Depositing a second CrCN / WC functional layer on the first CrCN / WC functional layer, wherein the process parameters are as follows: depositing a second CrCN nanolayer in the second CrCN / WC functional layer at a temperature of 480-500° C., an Ar partial pressure of 0.3-0.4 Pa, a CH4 partial pressure of 4-4.1 Pa, a N2 partial pressure of 1.6-1.7 Pa, a substrate bias of 53-57 V, a Cr target current of 155-165 A, and a disk speed of 3 r / min; and depositing a second WC nanolayer in the second CrCN / WC functional layer at a temperature of 480-500° C., an Ar partial pressure of 0.3-0.4 Pa, a CH4 partial pressure of 4-4.1 Pa, a N2 partial pressure of 1.6-1.7 Pa, a substrate bias of 53-57 V, a W target current of 195-205 A, and a disk speed of 3 r / min; S4, depositing the CrTaHfCN / CrCN / WC functional layer on the second CrCN / WC functional layer with the following deposition parameters: at a temperature of 480-500°C, an Ar partial pressure of 0.3-0.4Pa, a CH4 partial pressure of 5.5-5.6Pa, a N2 partial pressure of 2.6-2.7Pa, a substrate bias of 58-62V, a CrTaHf target current of 175-185A, and a large disk speed of 2.5r / min, a first CrTaHfCN nanolayer in the CrTaHfCN / CrCN / WC functional layer is deposited; at a temperature of 480-500°C, an Ar partial pressure of 0.3-0.4Pa, a CH4 partial pressure of 5.5-5.6Pa, a N2 partial pressure of 2.6-2.7Pa, a substrate bias of 58-62V, a CrTaHf target current of 175-185A, and a large disk speed of 2.5r / min, a first CrTaHfCN nanolayer in the CrTaHfCN / CrCN / WC functional layer is deposited; The third CrCN nanolayer in the CrTaHfCN / CrCN / WC functional layer was deposited at 480-500°C, an Ar partial pressure of 0.3-0.4Pa, a CH4 partial pressure of 5.5-5.6Pa, an N2 partial pressure of 2.6-2.7Pa, a substrate bias of 58-62V, a W target current of 195-205A, and a disk rotation speed of 2.5r / min. The third WC nanolayer in the CrTaHfCN / CrCN / WC functional layer was deposited at 480-500°C, an Ar partial pressure of 0.3-0.4Pa, a CH4 partial pressure of 5.5-5.6Pa, an N2 partial pressure of 2.6-2.7Pa, a substrate bias of 58-62V, a W target current of 195-205A, and a disk rotation speed of 2.5r / min. S5. Depositing a CrTaHfCN surface layer on the CrTaHfCN / CrCN / WC functional layer, with the following process parameters: temperature of 480-500°C, Ar partial pressure of 0.3-0.4Pa, CH4 partial pressure of 6-6.1Pa, N2 partial pressure of 2.6-2.7Pa, substrate bias of 63-67V, CrTaHf target current of 175-185A and disk speed of 2r / min.

Citation Information

Cited By

  • Cutter with multiple nano-coatings and preparation method thereof

    CN121161258A

  • Multi-layer coating cutter and preparation method thereof

    CN121183307A